Temperature Assessment on a Reclaimed Surface Mine During Northern Bobwhite Breeding Season: Considerations for Habitat Management - Donald M. Yow; Jeremy P. Orange; John J. Morgan; Gary Sprandel; Danna L. Baxley; Eric Williams (National Quail Symposium Proceedings, 2017)
Ground-level air temperatures were assessed within 4 distinct habitat areas on a managed reclaimed surface mine at Peabody Wildlife Management Area, Kentucky, 26 June–17 July 2015, during the northern bobwhite (Colinus virginianus) brood season. Habitat consisted of disked and nondisked areas of native grass and an invasive species, sericea lespedeza (Lespedeza cuneata). Disked areas offered more open space for bobwhite mobility and experienced higher average temperatures than nondisked sites. Although statistically significant, differences in air temperature between disked and nondisked areas were likely too small to have practical implications for bobwhite habitat management in Kentucky under current climatic conditions. This will likely change in the future as the regional climate warms and periods of excessive heat are more likely to occur. Consequently, managers may want to consider microclimate when making management decisions.
Keywords: Colinus virginianus; northern bobwhite; conservation; habitat management; Lespedeza cuneata; Peabody WMA; reclaimed surface mine; temperature